Immunogenicity and Protective Effect of a Virus-Like Particle Containing the SAG1 Antigen of Toxoplasma gondii as a Potential Vaccine Candidate for Toxoplasmosis - Choi, Won Hyung (Biomedicines, 2020)
This study was carried out to evaluate the vaccination effect of a virus-like particle (VLP) including the surface antigen 1 (SAG1) of Toxoplasma gondii as a potential vaccine for toxoplasmosis. The SAG1 virus-like particles (SAG1-VLPs) were expressed by Sf9 cells, and their expression was confirmed through cloning, RT-PCR analysis, and western blot method. The immunogenicity and vaccine efficacy of SAG1-VLPs were assessed by the antibody response, cytokine analysis, neutralization activity, splenocyte assay, and survival rates through a mouse model. In particular, IgG, IgG1, IgG2a, and IgA were markedly increased after immunization, and the survival rates of T. gondii were strongly inhibited by the immunized sera. Furthermore, the immunization of SAG1-VLPs effectively decreased the production of specific cytokines, such as IL-1β, IL-6, TNF-α, and IFN-γ, after parasite infection. In particular, the immunized group showed strong activity and viability compared with the non-immunized infection group, and their survival rate was 75%. These results demonstrate that SAG1-VLP not only has the immunogenicity to block T. gondii infection by effectively inducing the generation of specific antibodies against T. gondii, but is also an effective antigen delivery system for preventing toxoplasmosis. This study indicates that SAG1-VLP can be effectively utilized as a promising vaccine candidate for preventing or inhibiting T. gondii infection.